2019
DOI: 10.1177/0883073819881940
|View full text |Cite
|
Sign up to set email alerts
|

Serial Magnetic Resonance Imaging (MRI) in Pyruvate Dehydrogenase Complex Deficiency

Abstract: Objectives: To report 2 additional cases of pyruvate dehydrogenase complex deficiency with reversible deep gray matter lesions following initiation of ketogenic diet and to perform a literature review of serial imaging in patients with pyruvate dehydrogenase complex. Methods: Clinical data on 3 previously unpublished cases of patients with pyruvate dehydrogenase complex deficiency and with serial magnetic resonance imagings (MRIs) before and after institution of ketogenic diet were reported. A systematic liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…33 It is believed that female patients with prenatal onset PDHA1related disease, due to severe mutations and lack of residual enzyme activity, display a nonprogressive course and that interventions such as a ketogenic diet would not be effective given the lack of responsiveness on a cellular basis. 12 In our study, two of seven female patients with prenatal developmental and clastic lesions (#7,9) showed progression on repeated MRI-s with additional postnatal lesions. It's is therefore possible that the pathophysiological mechanism could be more of continuum and that a ketogenic diet might be effective also in girls with developmental lesions as has been previously suggested.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…33 It is believed that female patients with prenatal onset PDHA1related disease, due to severe mutations and lack of residual enzyme activity, display a nonprogressive course and that interventions such as a ketogenic diet would not be effective given the lack of responsiveness on a cellular basis. 12 In our study, two of seven female patients with prenatal developmental and clastic lesions (#7,9) showed progression on repeated MRI-s with additional postnatal lesions. It's is therefore possible that the pathophysiological mechanism could be more of continuum and that a ketogenic diet might be effective also in girls with developmental lesions as has been previously suggested.…”
Section: Discussionsupporting
confidence: 51%
“…The basal ganglia involvement in our study, with predominant involvement of the globi pallidi , is similar to previous studies 30,31 and differs from what has been described in other mitochondrial diseases where the lesions more commonly involve the striatum. Early diagnosis is important as the deep gray‐matter lesions could be reversible after introducing a ketogenic diet 4,12 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…KD treatment is therefore considered a treatment of choice for PDHC syndrome, and it has already been shown to lead to general improvements in some PDHC‐related neurological conditions: childhood‐onset epilepsy and recurrent episodes of paroxysmal dystonia and ataxia using the classic 4:1 or <4:1 KD ratios 80‐82 . In a recent serial brain MRI study, 83 patients with PDHC syndrome also demonstrated reversible deep gray matter lesions (basal ganglia) and clinical improvement following the initiation of a KD (here, the reported sum of serum ketones 3‐hydroxybutyrate and acetoacetate was >3 mM). Interestingly, partial or total replacement of KD with ketone bodies (ie, 3‐hydroxybutyrate) was also shown to improve the clinical condition in a small PDHC cohort, indicating that ketone bodies might constitute a potential adjuvant treatment to the KD, 84 which could help to improve KD compliance, diminish side‐effects and improve quality of life.…”
Section: Metabolic Epilepsy Related To Dysfunctional Energy Utilization: Pdhc Deficiencymentioning
confidence: 99%